Vaginal Vault Prolapse - Azubuike Uzoma; K. A. Farag (Obstetrics and Gynecology International, 2009)
Introduction. Vaginal vault prolapse is a common complication following vaginal hysterectomy with negative impact on women's quality of life due to associated urinary, anorectal and sexual dysfunction. A clear understanding of the supporting mechanism for the uterus and vagina is important in making the right choice of corrective procedure. Management should be individualised, taking into consideration the surgeon's experience, patients age, comorbidities, previous surgery and sex life. Result. Preexisting pelvic floor defect prior to hysterectomy is the single most important risk factor for vault prolapse. Various surgical techniques have been advanced at hysterectomy to prevent vault prolapse. Studies have shown the McCall's culdoplasty under direct visualisation to be superior. Vault prolapse repair rely on either the use of patient's tissue or synthetic materials and can be carried out abdominally or vaginally. Sacrospinous fixation and abdominal sacrocolpopexy are the commonly performed procedures, with literature in favour of abdominal sacrocolpopexy over sacrospinous fixation due to its reported higher success rate of about 90%. Other less commonly performed procedures include uterosacral ligament suspension and illiococcygeal fixation, both of which are equally effective, with the former having a high risk of ureteric injury. Colpoclesis will play a greater role in the future as the aging population increases. Mesh procedures are gaining in popularity, and preliminary data from vaginal mesh procedures is encouraging. Laparoscopic techniques require a high level of skill and experience. There are many controversies on the mechanism of prolapse and management techniques, which we have tried to address in this article. Conclusion. As the aging population increases, the incidence of prolapse will also rise, older techniques using native tissue will continue, while new techniques using the mesh needs to be studied further. The later may well be the way forward in future.